Puritan papers ; v. 2 - Packer, James Innell, 1926- (Phillipsburg, NJ Presbyterian and Reformed, 2001)
Contents : v. 1 : 1956-1959. Includes bibliographical references.
A Symposium of papers read at three annual Puritan and Reformed Studies Conferences, Westminster Chapel, London.
Keywords: Puritanism -- theology